Characterization of cassava (Manihot esculenta [Cranz]) genotypes sourced from different regions in southwestern Ethiopia using morphological traits - Semman, A.N.; Abebe, A.T.; Beyene, T.M.; Yusuf, R.I.; Abtew, W.G. (2025)
Phenotypic variability study in cassava is the primary and very important approach in understanding the genetic variation by breeding programs. The objective of study was to characterize 182 cassava germplasm. The experiment was laid in alpha lattice design with two replications. Nineteen qualitative and three quantitative traits were collected at the 3rd, 6th and 9th months growing stages after planting. The data were subjected to diversity analysis techniques including Shannon diversity index and multivariate analysis (clustering, correlation and principal component analyses). The Shannon index revealed high variability within the genotypes for petiole color (1.56), color of stem exterior (1.41), leaf retention (1.37), color of leaf vein (1.26), color of stem epidermis (1.05) and color of stem cortex (1.04). The correlation analysis exhibited a significant (p = 0.05) positive correlation between vein color and petiole color (0.73), petiole length and width of leaf lobe (0.6), width of leaf lobe and length of leaf lobe (0.66). Cluster analysis grouped the studied germplasm into four divergent groups. The principal component analysis revealed the first five dimensions with Eigen values > 1 explained 65.15% of the total variations, while the first three principal components explained 48.64% of the total variation. Some genotypes displayed values out of the range specified in the cassava descriptor, thus indicating the need to updating the cassava descriptor. Generally, this study revealed high genetic variability in the studied germplasm and provides invaluable information for the future genetic improvement and conservation of the crop.